Desvendando a lógica Fuzzy - Silva, Flávio Fernandes Barbosa (2011)
The purpose of this Master Dissertation is to build an algorithm which executes the Fuzzy Rule-Based System (FRBS) procedures. To reach this aim, it will be rstly studied the basic concepts of fuzzy set theory along with all FRBS components. After that, the computer codes that exihibit step-by-step some techniques for solving several problems using this powerful tool are going to show. Such a tool is widespread in Matlab. Promoting and spreading the accessibility to that tool is the intention of this work. It will be made through the presentation of several codes, which were developed in this dissertation. These codes do not depend on a specic computer package. The algorithm can be implemented in any existing programming language like C, for example. The programming of the algorithm can be made in Octave environment, too. Octave is similar to MATLAB; besides, it is a free software. Making dynamic adjustments of the FRBS parameters is an advantage of the algorithm developed here compared with MATLAB one. Note that any adjustments can be easily made while the code is running.